Predictive value of brain atrophy, serum biomarkers and information processing speed for early disease progression in multiple sclerosis - Oset, Magdalena; Domowicz, Małgorzata; Wildner, Paula; Siger, Małgorzata; Karlińska, Iwona; Stasiołek, Mariusz; Świderek-Matysiak, Mariola (Frontiers in Neurology, 2023)
Introduction: Multiple sclerosis (MS) is a chronic autoimmune-mediated demyelinating disease of the central nervous system (CNS). Clinical presentation of the disease is highly differentiated even from the earliest stages of the disease. Application of stratifying tests in clinical practice would allow to improve clinical decision making including proper assessment of treatment benefit/risk balance. Methods: This prospective study included patients with MS diagnosis established up to one year before recruitment. We analyzed serum biomarkers such as CXCL13, CHI3L1, OPN, IL6, GFAP and neurofilament light chains (NfL), brain MRI parameters of linear atrophy: bicaudate ratio (BCR), third ventricle width (TVW) as well as information processing speed measured with Symbol Digit Modalities Test (SDMT) during the two years follow-up. Results: The study included a total of 50 patients recruited shortly after establishment of MS diagnosis (median 0 months; range 0-11 months), the mean time of observation was 28 months (SD=4.75). We observed a statistically significant increase in EDSS score (Wilcoxon test: Z=3.06, p=0.002), BCR (Wilcoxon test: Z=4.66, p<0.001) and TVW (Wilcoxon test: Z=2.84, p=0.005) after two years of disease. Patients who had significantly higher baseline level of NfL suffered from more severe disease course in EDSS score (U Mann-Whitney test: U=107, Z= -2,74, p= 0.006) and presence of relapse (U Mann-Whitney test: U=188, Z= -2.01, p= 0.044). In the logistic regression model none of the parameters was a significant predictor for the achieving of no evidence of disease activity status (NEDA). In the model considering all of the assessed parameters only the level of NfL had a significant impact on disease progression measured as the increase in EDSS (logistic regression: β=0.002, p=0.017). Conclusions: We confirmed that NfL levels in serum are associated with more active disease. Moreover, we found that TVW at the time of diagnosis was associated with impairment in cognitive function measured by information processing speed at the end of two years observation. Inclusion of serum NfL and TVW assessment early in the disease may be a good predictor of disease progression independent from NEDA.